Bringing ritual to mind : psychological foundations of cultural forms - McCauley, Robert N. (Cambridge University Press, 2002)
Bringing Ritual to Mind explores the psychological foundations of religious rituals. Religious rituals exploit either high performance frequency or extraordinary emotional stimulation (but not both) to enhance recollection. McCauley and Lawson use a wide range of evidence to argue that the explanation lies in participants' cognitive representations of ritual form.